Association between sleep quality and pre-hemodialysis blood pressure among patients undergoing hemodialysis: A cross-sectional study - Robiatul Adawiyah; Dwi Soelistyoningsih; Achmad Rifai; Wira Daramatasia; Angernani Trias Wulandari (Lentera Perawat, 2026)
Background: Chronic kidney disease (CKD) is an ailment of kidney function that develops gradually and in advanced stages requires long-term hemodialysis therapy. Sleep disturbances are common among patients due to both physiological and psychological factors. Pourer sleep quality may elevate the sympathetic nervous system's responsiveness, disrupt fluid balance, and contribute to elevated blood pressure, particularly pre-hemodialysis blood pressure, which reflects the patient’s hemodynamic status prior to dialysis initiation. Objective: This study aimed to assess the association between sleep quality and pre-hemodialysis blood pressure, including systolic and diastolic, in patients undergoing hemodialysis. Methods: This research utilized a quantitative, cross-sectional methodology that was conducted in September 2025 at the Hemodialysis Unit of Universitas Muhammadiyah Malang Hospital, among 80 patients selected using purposive sampling, undergoing routine hemodialysis for at least three months at Universitas Muhammadiyah Malang Hospital,  who were conscious and able to communicate verbally. The Pittsburgh Sleep Quality Index (PSQI) questionnaire was utilized to assess quality of sleep, whereas pre-hemodialysis blood pressure including systolic and diastolic measurements was weighed prior to the dialysis procedure using a standard sphygmomanometer. Data were evaluated using the Spearman Rank test, with an established significance threshold of p <0.05. Results: Of the total respondents, 42 (52.5%) had good sleep quality, while 38 (47.5%) experienced poor sleep quality. The median pre-hemodialysis blood pressure was 130/80 mmHg, indicating stage 1 hypertension. Statistical assessment disclosed a significant association between quality of sleep and pre-hemodialysis blood pressure category (p = 0.014) with a weak positive correlation (r = 0.274), revealing that poorer sleep quality was associated with higher blood pressure category, although the effect size was small. Conclusion: Sleep quality is significantly associated with blood pressure in patients of pre-hemodialysis. Poorer sleep quality leads to be collaborated with higher blood pressure. However, the weak correlation (r = 0.274) suggests that sleep quality is one of several contributing factors to blood pressure variability in this population. These verdicts highlight the significance of assessing and managing sleep quality as part of comprehensive care in hemodialysis patients.